2003
DOI: 10.4141/a02-052
|View full text |Cite
|
Sign up to set email alerts
|

Defining the effects of wheat type, water inclusion level, and wet-diet restriction on variability in performance of broilers fed wheat-based diets with added water

Abstract: Scott, T. A. and Silversides, F. G. 2003. Defining the effects of wheat type, water inclusion level, and wet-diet restriction on variability in performance of broilers fed wheat-based diets with added water. Can. J. Anim. Sci. 83: 265-272. The objectives of the study were to determine if feed conversion ratio (FCR) in broilers fed wet Hard Red Spring (HRS) as compared to Durum-based wheat diets could be reduced by: (a) diluting HRS with Durum wheat, (b) pelleting of the wheat, (c) adding different levels of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
3
6
0
1
Order By: Relevance
“…They reported that BW of of Muscovy ducklings fed wet feed was 1.97 and 3.12% higher than that of birds fed dry mash feed and the BWG of the birds fed wet feed was 6.91 and 10.72% higher than that of the birds fed dry mash feed. Similar observations have been reported in growing quails and broilers (Scott and Silversides, 2003;Afsharmanesh et al, 2006;Syafwan et al, 2011;Farghly, 2012;Afsharmanesh et al, 2016;Mortazavi and Afsharmanesh 2017). However, Beg, et al, (2011) reported no difference in bird body weight and gain.…”
Section: Results and Discussion 1-body Weight (Bw) And Gain (Bwg)supporting
confidence: 81%
“…They reported that BW of of Muscovy ducklings fed wet feed was 1.97 and 3.12% higher than that of birds fed dry mash feed and the BWG of the birds fed wet feed was 6.91 and 10.72% higher than that of the birds fed dry mash feed. Similar observations have been reported in growing quails and broilers (Scott and Silversides, 2003;Afsharmanesh et al, 2006;Syafwan et al, 2011;Farghly, 2012;Afsharmanesh et al, 2016;Mortazavi and Afsharmanesh 2017). However, Beg, et al, (2011) reported no difference in bird body weight and gain.…”
Section: Results and Discussion 1-body Weight (Bw) And Gain (Bwg)supporting
confidence: 81%
“…It is apparent from this increase in feed intake with wet feeding that limitations in intake exist with both samples of wheat. In previous studies (Scott 2002;Scott and Silversides 2003), adding water to HRS-based diets caused disproportionate increases in feed intake and growth resulting in a marked increase in FCR, whereas adding water to Durumbased diets resulting in proportionate changes in feed intake and growth, with no changes in FCR. The wheat samples used in the present study were not the same as those used previously and were evaluated with different lots of birds, perhaps explaining differences between previous studies and this one, particularly for HRS wheat.…”
Section: Discussionmentioning
confidence: 88%
“…Although supplemental enzymes resulted in increased intake of the diets, this supplementation did not negate differences in growth rate between sources of wheat or its relationship to feed intake. Subsequent studies (Scott 2002;Scott and Silversides 2003) suggested that intake of wheat-based diets may be limited by the hydration rate of the diet in the gut. The time required for hydration of different sources of wheat in the gut directly influences digesta passage time and subsequently feed intake (Yasar and Forbes 2000).…”
mentioning
confidence: 99%
“…The advantages of wet feeding in broilers were recently reviewed by Yasar and Forbes (2000) and wet feeding was suggested by Scott, 2002 , Scott and Silversides, 2003 and Afsharmanesh et al. (2006) as being a valuable tool in increasing our understanding of the limitations in feed intake by broilers fed cereal-based diets.…”
Section: Introductionmentioning
confidence: 99%